2009
DOI: 10.1161/strokeaha.108.516682
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Functioning of Spouses of Patients With Stroke From Initial Inpatient Rehabilitation to 3 Years Poststroke

Abstract: Background and Purpose-Few studies have focused on long-term changes in the caregiving experience after stroke. This study assessed changes in the psychosocial functioning of spouses (burden, depressive symptoms, harmony in the relationship between patient and spouse, and social relations) during the first 3 years after stroke and identified predictors of the course of spouses' psychosocial functioning based on the characteristics of patients and spouses with special emphasis on coping style. Methods-We examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
115
3
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(133 citation statements)
references
References 29 publications
(27 reference statements)
11
115
3
4
Order By: Relevance
“…A previous study (25) , like the present study, did not identify any association of the age or sex of the carer with the presence of overload. There was, however, an association between the presence of psychiatric symptoms and the increase in overload.…”
Section: Financial Difficulties Are Another Problem Reportedcontrasting
confidence: 58%
“…A previous study (25) , like the present study, did not identify any association of the age or sex of the carer with the presence of overload. There was, however, an association between the presence of psychiatric symptoms and the increase in overload.…”
Section: Financial Difficulties Are Another Problem Reportedcontrasting
confidence: 58%
“…Older patients report stroke having a greater impact on physical functioning. Further, female caregivers had a significantly lower QoL than male caregivers, similar to the findings of other authors [4,22]. In a sample of 215 caregivers, Marco et al2 found that the negative impact of caring for a stroke patient is greater in middle-aged female caregivers, and that depression and musculoskeletal pain in the caregiver, time spent caring and degree of disability of the care recipient are influential factors in this deterioration in QoL.…”
Section: Discussionsupporting
confidence: 70%
“…This reality has a negative impact on the quality of life (QoL) of patients and also of their relatives, who usually become their main caregivers [2]. Taking on the caregiving role is a significant source of stress, increasing the caregivers' risk of developing various physical and mental health problems [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…This figure underlines the extent of the burden of care that partners carry [26] [27]. Particularly partners who face the loss of communication abilities in their family member due to aphasia may struggle [28].…”
Section: Rationale For the Implementation Of A Cpt Programmementioning
confidence: 97%
“…Partners are sharing the hope for recovery and want to contribute to this improvement by promoting this treatment or even by becoming co-therapists. Hallé and Le Dorze [33] concluded that partners who were interviewed around three months post stroke, were seeking information to satisfy their caregiver needs, but disregarded their personal needs or relational needs, such as good 27 communication with their aphasic partner. Interestingly, the partners recruited in our study had been living with someone with aphasia for an average of 11.5 months and their perspective had changed.…”
mentioning
confidence: 99%